Modulation of NETosis in Swine Neutrophil–Spermatozoa Co-Cultures In Vitro: Effects of Butylated Hydroxytoluene, Albumin, Prostaglandin E2, and Seminal Plasma - Fabiola Zambrano; Felipe Pezo; André Furugen Cesar de Andrade; Rodrigo Rivera-Concha; Pamela Uribe; Mabel Schulz; Henricco Zapparoli; Luan Mendes de Oliveira Bezerra; Carlos Hermosilla; Anja Taubert; Raúl Sánchez (Antioxidants, 2025)
In swine reproduction, immune-mediated mechanisms such as neutrophil extracellular trap (NET) formation can affect sperm function and reduce fertility outcomes. This study evaluated the capacity of antioxidant and reproductive compounds—butylated hydroxytoluene (BHT), prostaglandin E2 (PGE2), bovine serum albumin (BSA), and seminal plasma (SP)—to modulate NETosis in co-cultures of swine neutrophils and cryopreserved spermatozoa. NET formation was quantified by nuclear area expansion and validated by digital cytometry and immunofluorescence. BHT (0.5 mM) and PGE2 (10 µM) produced the most significant inhibitory effects, reducing NETotic cell percentages from 34.5 ± 2.7% (sperm-exposed controls) to 12.2 ± 1.3% and 14.5 ± 2.1%, respectively (p < 0.01). SP at 20% decreased NETosis to 16.8 ± 1.8%, while BSA (0.5%) achieved a moderate reduction to 21.3 ± 2.5%. Flow cytometry revealed reduced peroxynitrite levels in sperm treated with SP and BSA. Two NET phenotypes (aggNETs and sprNETs) were identified. BTS medium enhanced NET formation, whereas DNase I degraded NETs effectively. These findings identify porcine NETosis as a redox-sensitive pathway modulated in vitro, suggesting an immunological role in enhancing sperm preservation for swine artificial insemination.